2022
DOI: 10.3390/rs14205249
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sentinel-2 and Landsat 8 for Burn Severity Mapping in Western North America

Abstract: Accurate assessment of burn severity is a critical need for an improved understanding of fire behavior and ecology and effective post-fire management. Although NASA Landsat satellites have a long history of use for remotely sensed mapping of burn severity, the recently launched (2015 and 2017) European Space Agency Sentinel-2 satellite constellation offers increased temporal and spatial resolution with global coverage, combined with free data access. Evaluations of burn severity derived from Landsat and Sentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…Sentinel-2 (MSI) data can be recommended as a key Earth observation data source in forest resources assessment and monitoring [34]. Howe et al [35] assess the accuracy of Sentinel-and Landsat-derived burn indices for 26 fires that burned between 2016 and 2019 in western North America. They concluded that burn severity mapping could significantly benefit from the integration of Sentinel imagery to Landsat-forest surveillance data by increasing imagery availability (image every 5 days), and that Sentinel's higher spatial resolution can improve opportunities for inspecting finer-scale fire impact across ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Sentinel-2 (MSI) data can be recommended as a key Earth observation data source in forest resources assessment and monitoring [34]. Howe et al [35] assess the accuracy of Sentinel-and Landsat-derived burn indices for 26 fires that burned between 2016 and 2019 in western North America. They concluded that burn severity mapping could significantly benefit from the integration of Sentinel imagery to Landsat-forest surveillance data by increasing imagery availability (image every 5 days), and that Sentinel's higher spatial resolution can improve opportunities for inspecting finer-scale fire impact across ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…No study has been published for the 2021 Muli fire, and the area burned in Muli County in 2021 has not been monitored in the remote sensing fire product MOD14A2 resolution due to its large spatial resolution (1 km). Therefore, this method can extract the burning area of smaller fires more accurately, but the extraction accuracy is lower for larger fires such as the 2019 fire, which may be potentially due to fire having heterogeneous effects at scales finer than 30 m, particularly in non-stand replacing fires, resulting in high sub-pixel variability in tree mortality ( Schroeter & Foster, 2004 ; Howe et al, 2022 ) and frequency of smaller-sized unburned patches. However, the larger the area, the greater the heterogeneity of fire images presented, so it is also a question of whether to choose a more accurate way, such as deep learning, to extract the burning area in the method for a higher spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies using the decision tree to build a combination of the burning index and OTSU thresholds to extract burned areas ( Tianchi, Fuqin & Yan, 2020 ; Li et al, 2021a ; Tang et al, 2021 ; Tian et al, 2022 ), which can achieve better accuracy results. There are also comparative studies on the extraction of the burned area from Sentinel-2 and Landsat 8 data sources, and they found that Sentinel generally performed as well or better than Landsat for four spectral indices of burn severity and that Sentinel’s higher spatial resolution improves opportunities for examining finer-scale fire effects across ecosystems ( Mallinis, Mitsopoulos & Chrysafi, 2018 ; Zhang et al, 2019 ; Howe et al, 2022 ). However, the extraction and evaluation of burned areas with different damage using Sentinel-2 are lacking, so assessing the method’s applicability is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to a number of variables, including the spatial resolution of Landsat images, the radiometric resolution of the sensors used during the time of these studies being inadequate to capture the slight variations in radiance, and the lack of spectral bands in the red-edge region. Previous research has shown slight improvement in the performance of Sentinel-2 NBR-based indices when compared to Landsat 8 NBR-based indices [24,25]. However, this research was limited to indices that could be calculated by both sensor systems, which eliminates the use of red-edge indices.…”
Section: Spectral Indices' Ability To Estimate Field Measurementsmentioning
confidence: 98%